PENAKSIR RASIO REGRESI LINEAR YANG EFISIEN UNTUK RATA-RATA POPULASI DENGAN MENGGUNAKAN DUA VARIABEL TAMBAHAN - Edi Jamilun; Harison '; Haposan Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This paper discusses three ratio regression linear estimators by Singh, Upadhyaya  and Premchandra for population mean Y using two auxiliary variables X and Z on simple random sampling which is a review of article “An Improved Version of Regression Ratio Estimator with Two auxiliary Variables in Sample Surveys”. The three estimators are biased then the minimum of the (MSE) is determined. Furthermore, their MSE are compared to each other. This comparison shows that the estimator with the minimum MSE is the most efficiensi estimator.